Product Marketing Strategy Using Digital Marketing Technology - Susanti, Leni (Yayasan Gema Bina Nusantara, 2025)
The rapid evolution of digital technology and social media has significantly influenced product marketing strategies, enabling businesses to engage with a broader audience more efficiently. Digital marketing, combined with social media platforms, has become a vital tool for increasing brand awareness, customer interaction, and sales conversion rates The research highlights key digital marketing techniques, including search engine optimization (SEO), social media marketing (SMM), content marketing, email marketing, and pay-per-click (PPC) advertising. These methods enable businesses to increase brand awareness, improve customer engagement, and optimize sales conversions. Additionally, the study discusses the role of data analytics and artificial intelligence (AI) in personalizing marketing strategies, predicting consumer behavior, and enhancing decision-making processes. The findings indicate that integrating digital marketing into product marketing strategies significantly improves market reach, customer retention, and return on investment (ROI). Businesses that leverage digital tools effectively can achieve competitive advantages by adapting to evolving consumer preferences and market trends. This paper concludes that digital marketing technology is an essential component for businesses aiming to enhance their product marketing effectiveness in the digital era.